ANALYSIS OF CYBERBULLYING DISCOURSE: LINGUISTIC AND SOCIOLOGICAL PERSPECTIVES IN UNCOVERING POWER DYNAMICS IN CYBERSPACE: ANALISIS WACANA CYBERBULLYING: PERSPEKTIF LINGUISTIK DAN SOSIOLOGI DALAM MENGUNGKAP DINAMIKA KEKUASAAN DI DUNIA MAYA - Oman Sukmana; Mukhrizal Arif; Indra (SOSIOEDUKASI, 2025)
The purpose of the research is to analyze in depth the representation of power dynamics and social hierarchy in cyberbullying through discourse patterns and communication strategies. The research also seeks to explain how social norms or power structures in the real world are replicated and strengthened in online interactions involving cyberbullying. The uniqueness of the research is that it integrates linguistic and sociological perspectives comprehensively, in contrast to previous research that tends to focus on one of the disciplines, in order to offer a holistic analysis of the phenomenon of cyberbullying. This study adopts the narrative literature review method, a systematic qualitative approach to identify, evaluate, and synthesize findings from previous studies related to the representation of women in Indonesian horror films. The findings of the study show that cyberbullying is a multidimensional phenomenon that involves the complexity of language, social interaction, and power structures in the digital realm. Cyberbullying, which manifests itself in many forms, inherently reflects the power imbalance between perpetrator and victim, often reinforced by the anonymity and wide reach of  digital platforms. However, the resistance of discourse and power back shows that victims are not always passive, but are able to implement linguistic strategies to challenge this dominance, restore agency, and even encourage social change.